Enhancing autophagy leads to increased cell death in radiation-treated cervical cancer cells - Ji Geun Yoo; Yoon Kyung Lee; Keun Ho Lee (Taylor & Francis Group, 2023)
This study was carried out to determine the effect of autophagy modulation in radiation treatment of cervical cancer cells. HeLa and CaSki cells were irradiated with γ-rays (2 Gy/min) after treatment with an autophagy inducer (rapamycin) and inhibitor (3-MA). Expression of LC3 and cell death in two cell preparations were examined. In addition, expression of Caspase-3 and PARP were examined after radiation alone and with autophagy inhibitor treatment. A notable increment of LC3 expression was detected after radiation in both cell lines. Cell viability was observed to decrease in 3-MA-treated cells compared to radiation alone, and even further in rapamycin-treated cells. Apoptosis was confirmed to occur later than autophagy in radiation treatment, and inhibition of autophagy derived a decrease in apoptosis. In conclusion, radiation-induced autophagy may be regulated by modulators, and autophagy augmentation yields an increase in cervical cancer cell death under radiation.Impact statement What is already known on this subject? Autophagy is known to contribute both to tumour cell survival and death against radiation therapy. The effect of induction or inhibition of radiation-induced autophagy on cervical cancer cell death is not clear. What the results of this study add? Cell viability was observed to decrease in 3-MA-treated cells compared to radiation alone, and even further in rapamycin-treated cells. Apoptosis occurred later than autophagy in radiation treatment, and inhibition of autophagy derived a decrease in apoptosis. What the implications are of these findings for clinical practice and/or further research? Our results suggest that radiation-induced autophagy may be regulated by modulators, and autophagy augmentation yields an increase in cervical cancer cell death under radiation.